Фактори відтворення привласнення інформаційно-цифрового інтелектуального продукту у сфері виробництва засобів виробництва - Леонідов, Ігор Леонідович (Придніпровська державна академія будівництва та архітектури, Дніпро, 2024)
UKR: У статті розкрито варіант екстерналізації привласнення інформаційно-цифрового інтелектуального продукту в сфері виробництва засобів виробництва національної економіки України. З'ясовано, що в процесі виробничого використання інтелектуальний продукт проходить стадії кругообігу капіталу в формах: грошовій, виробничій та товарній. Підтверджено, що в такому послідовному русі відтворюються особливості, характерні інтелектуальному капіталу, як різновиду капіталу. Виділено наступні ознаки капіталу в уречевленому та олюдненому інтелектуальному продукті: призначення для споживання у якості фактора або умови виробництва; здатність забезпечити прийнятний доход на авансований капітал, пропорційно альтернатив за ризиком авансування. Окреслена підпорядкованість відтворення привласнення інтелектуального продукту як закономірностям функціонування його мережі, так і процесам, що протікають в сфері циркуляції капіталу. Розкрито фактори відтворення привласнення інформаційно-цифрового інтелектуального продукту, обумовлені функціоналом грошового, виробничого та товарного капіталу у сфері виробництва засобів виробництва. Практична значимість визначена в придатності для державного регулювання відтворення привласнення інформаційно-цифрового інтелектуального продукту при удосконалення стратегії повоєнного відновлення національної економіки України.

ENG: The paper discusses of externalization of appropriation of informatively-digital intellectual product in the sphere of production of measure production into national economics of Ukraine. The aim of this research is an open of factors of reproduction of appropriation of the informatively-digital intellectual product, what conditioned by the functional of money, productive and commodity capital. A variant of integration method was used for achieving of the aim of the research. The informatively-digital intellectual product takes part in the circulation of money, productive and commodity capital into the process of its (of the product) productive use was found out. Reproduction of specific, what characterizes of the intellectual capital, how the variety of capital was confirmed in marked circulation. Signs of capital into materialized and humanized of intellectual product were dissociated, namely: appointing for consumption how a factor or condition of production; possibility to provide an acceptable income on the advanced capital, proportionally alternatives per by risk of advancing. Subordination of reproduction of appropriation of informatively-digital of intellectual product was outlined for trends of functioning of its network and for processes into sphere of circulation of capital. The factors of reproduction of appropriation of informatively-digital intellectual product, what determined by the functional of money, productive and commodity capital in the sphere of production of means of production were exposed. Further researches must be goal-seeking to the formalization (with accounting of proposed factors) of reproduction of appropriation of informatively-digital intellectual product into sphere of production of means of production for the improvement of strategy of post-war renewal of national economics of Ukraine. Practical importance of the paper was represented in availability for government regulation of reproduction of appropriation of informatively-digital intellectual product and improvement of strategy of post-war renewal of national economy of Ukraine.
Factors of Reproduction of Appropriation of Informatively-Digital IntellectuaL Product into Sphere of Production of Means of Production
І. Леонідов: ORCID 0000-0001-7369-2464
Keywords: інтелектуальна власність; привласнення; інформаційно-цифровий інтелектуальний продукт; інтелектуальний капітал; відтворення; інноваційна економіка; intellectual ownership; appropriation; informatively-digital intellectual product; intellectual capital; reproduction; innovation economics; КМЕіСГД; LAW/JURISPRUDENCE::Private law::Intellectual property law; SOCIAL SCIENCES::Business and economics